Computational and statistical methods for protein quantification by mass spectrometry - Eidhammer, Ingvar; Barsnes, Harald; Eide, Geir Egil.; Martens, Lennart (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
The definitive introduction to data analysis in quantitative proteomics This book provides all the necessary knowledge about mass spectrometry based proteomics methods and computational and statistical approaches to pursue the planning, design and analysis of quantitative proteomics experiments. The author's carefully constructed approach allows readers to easily make the transition into the field of quantitative proteomics. Through detailed descriptions of wet-lab methods, computational approaches and statistical tools, this book covers the full scope of a quantitative experim.
4.7.1 Constructing the decoy database4.7.2 Separate or composite search; 4.8 Exercises; 4.9 Bibliographic notes; 5 Protein quantification by mass spectrometry; 5.1 Situations, protein, and peptide variants; 5.1.1 Situation; 5.1.2 Protein variants -- peptide variants; 5.2 Replicates; 5.3 Run -- experiment -- project; 5.3.1 LC-MS/MS run; 5.3.2 Quantification run; 5.3.3 Quantification experiment; 5.3.4 Quantification project; 5.3.5 Planning quantification experiments; 5.4 Comparing quantification approaches/methods; 5.4.1 Accuracy; 5.4.2 Precision; 5.4.3 Repeatability and reproducibility.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Proteomics -- Statistical methods; Mass spectrometry -- Data processing; SCIENCE -- Life Sciences -- Biochemistry; Proteomik; Masspektrometri; Electronic books; Electronic books